(untitled) (Stato, Chiese e pluralismo confessionale, 2018)
SOMMARIO: 1. Carcere e religione - 2. Pluralismo religioso e istanze di sicurezza - 3. Strategie di contrasto al proselitismo e alla radicalizzazione jihadista - 4. Gli ‘indicatori sulla radicalizzazione’ - 5. Le questioni aperte: prevenzione e de-radicalizzazione - 6. Cosa fare. Between religious freedom and security issues: the prevention of jihadist radicalisation in prison ABSTRACT: Faith constitutes an essential aspect of prison life. Its relevance has been emphasised in recent times because of the religious pluralism that characterises the current prison population. In this scenario, the rise of jihadist terrorism has shed light on the problem of radicalisation in prison, already known and studied by the experts, which poses new challenges for policymakers, prison staff, and detainees. Prison Administration has been focused on religious freedom, its boundaries and its relationship with religious extremism and has already adopted some measures to combat and monitor jihadist proselitism in Italian prisons. This paper provides an overview of these anti-radicalisation strategies in prisons, highlighting unresolved issues. These include the lack of an integrated plan with regards to prevention of radicalisation and de-radicalisation, not limited by the prison context. This paper further highlights the challenges in devising policies that address security concerns without sacrificing religious freedom and diversity, as provided for by the Constitution.